Pharmacognostic evaluation and antimicrobial activity of Pteridium aquilinum (L.) Kuhn leaves (Onocleaceae) via in vitro and in silico perspectives - Oluwatoyin Temilolu Adebayo; Bolaji Bosede Oluremi; Akingbolabo Daniel Ogunlakin; Gideon Ampoma Gyebi; Mubo Adeola Sonibare (PLoS ONE, 2025)
Background and objective Traditionally, Pteridium aquilinum L. has been utilized as medicine for ages, however, it is not listed in the Nigerian herbal pharmacopeia, and there is no information regarding its standardization and antimicrobial activity. Therefore, the purpose of this study was to examine the pharmacognostic parameters and antimicrobial activity of Pteridium aquilinum leaf. Methods Macroscopy, chemo-microscopy, fluorescence, and microscopic analyses of the leaf were investigated using standard methods. Qualitative and quantitative phytochemical screening, thin layer chromatography (TLC), GC-MS, and FTIR were also determined using standard procedures. Antioxidants were evaluated using DPPH. The antimicrobial activities of methanol extract and fractions were evaluated using Agar well diffusion method against Candida albicans, Aspergillus niger, Staphylococcus aureus, Salmonella Typhimurium, Escherichia coli, and Pseudomonas aeruginosa. The macroscopic features of P. aquilinum leaf include a bi-pinnate leaflet and alternate pinna arrangement. The GC-MS-identified compounds in the most active (DCM fraction) were docked against Candida albicans Sterol 14-alpha demethylase (5TZ1) and Escherichia coli DNA gyrase subunit B (6YD9). Results The macroscopic features and microscopic features such as anomocytic stomata, numerous stomata in the abaxial layer, and absence of stomata in the adaxial layer were observed. Chemomicroscopy of the powdered leaves shows that the leaf contains tannins, starch, and lignin. GC-MS detected eighteen compounds. The antimicrobial test revealed that the dichloromethane fraction of P. aquilinum leaf was most active on all the test strains (bacteria and fungi) at 25 mg/mL to 100 mg/mL concentrations. Through in silico research, the binding of 1,2-benzenedicarboxylic acid, (4-hydroxybenzoyl) hydrazine, octadecadienoyl chloride, and 11,14-Eicosadienoic acid, detected in the DCM fraction by GC-MS analysis, to the active sites of 5TZ1 and 6YD9 was stable. Conclusion This research gave scientific credence to the traditional medical practice of treating infections with P. aquilinum leaves.